Cognitive skills and executive neuropsychological functions in bilingual children (native language- castilian) and monolinguals castilian - Canales Gabriel, Ricardo (2017)
The study sought to establish whether there are differences in levels of cognitive skills development and executive functions in bilingual children and Spanish monolingual children, belonging to the same socio-economic level. Twenty students from 5th and 6th grades of the Community of Socos were examined; 24 students of 5th and 6th grade of the educational institution "Virgen del Carmen", Pilacucho, Huamanga; 24 students from the I.E. intercultural bilingual: "Shipiba Community" in Cantagallo, Lima; and 18 students of 5 ° and 6 ° degree of "Santa Rosa de America" of Callao; with ages ranging from 10 to 12 years.They were examined intelligence with the Raven Test and executive neuropsychological functions with some subtests of BANFE (Flores-Ostrosky, 2012). The results showed significant differences between the groups, both in cognitive functioning and executive functions. The students who yielded the lowest in both variables were the children of Socos, Ayacucho, rural and Quechua-speaking. Then the students of Huamanga, capital of the department of Ayacucho. The best performers were students from Callao and children from the Shipiba community of Cantagallo-Lima, influenced by other types of bilingualism.It is noted that dysortogenic factors: extreme poverty, social marginalization, and the problem of Quechua-Castilian bilingualism, would be related to cognitive development and executive functions in children. In conclusion, we found significant differences between groups of students from different socio-cultural realities at the level of executive neuropsychological functions and cognitive abilities.